Life-Threatening Adverse Events Following Therapeutic Opioid Administration in Adults: Is Pharmacogenetic Analysis Useful? - Parvaz Madadi; Johanna Sistonen; Gregory Silverman; Rebecca Gladdy; Colin J Ross; Bruce C Carleton; Jose C Carvalho; Michael R Hayden; Gideon Koren (Pain Research and Management)
BACKGROUND: Systemic approaches are needed to understand how variations in the genes associated with opioid pharmacokinetics and response can be used to predict patient outcome. The application of pharmacogenetic analysis to two cases of life-threatening opioid-induced respiratory depression is presented. The usefulness of genotyping in the context of these cases is discussed.